Peran Informasi ESG dalam Pengambilan Keputusan Investasi: Tren Global dan Tinjauan Literatur - Niken Rahmawati (MDP Student Conference, 2026)
Recent developments in capital markets indicate that investors no longer rely solely on financial information when making investment decisions, but increasingly consider non-financial information, particularly environmental, social, and governance (ESG). This article aims to review the literature discussing the role of ESG information in investment decision-making within capital markets. A narrative literature review method was employed by examining relevant national and international journal articles. The findings suggest that ESG information is commonly used as complementary information to financial data, providing additional insights into company characteristics, risk management, and long-term prospects. The literature also highlights the importance of ESG information quality, especially in terms of relevance, comparability, and transparency. Furthermore, the use of ESG information varies depending on investor characteristics and market context. Overall, ESG information has become an integral part in modern investment practices, although its application remains diverse.